IMPLEMENTATION OF THE DIGITAL POPULATION IDENTITY (IKD) APPLICATION IN THE CHILD IDENTITY CARD (KIA) MAKING SERVICE - Sholikha, Fazatul Imro'atus; Riyadh, Ahmad (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to determine the implementation of the Digital Population Identity (IKD) Application in the service of making Child Identity Cards (KIA) in Sidoarjo Regency. The background of the research is based on efforts to digitize population administration to improve the efficiency and convenience of public services. Method: The method used is descriptive qualitative with observation, interview, and documentation techniques. The analysis refers to the implementation theory of George C. Edward III's implementation theory which includes communication, resources, disposition, and bureaucratic structure. Results: The results showed that although IKD facilitates the process of making KIA through digital features such as self-activation and printing on the ADM machine, the implementation is still not optimal. The main obstacles include low public understanding, limited human resources. Novelty: The novelty of this research lies in the focus of analysis on the implementation of IKD in KIA services and the importance of increasing digital literacy, training officers, and strengthening SOPs in supporting the digital transformation of population services.